KEANEKARAGAMAN SERANGGA PERTANAMAN JAGUNG PADA LAHAN SAWAH DESA RANDUPADANGAN GRESIK JAWA TIMUR - Nisa, Isnaini Lailatun; Windriyanti, Wiwin; Nirwanto, Herry (Universitas Lampung, 2025)
Diversity of insect on agricultural land is an indicator of ecosystem balance which is the basis of the concept of Integrated Pest Management (IPM). The research was conducted in October-December 2022 on corn fields in Randupadangan Hamlet, Randupadangan Village, Menganti District, Gresik Regency. The research used survey method and purpose sampling. Insect sampling used 4 methods, namely sweep net, visual observation, yellow sticky trap, and pitfall trap. Determination of insect visits using scan sampling method. Data analysis used includes diversity index, evenness index, dominance index and association index with the help of Microsoft Excel. The results showed that the values of diversity index, dominance index, and evenness index were low, and the association index showed an association between species. The most active visiting time of insect visitors is in the morning, afternoon and afternoon, respectively. There are four roles of insects found, namely natural enemies, pests, pollinators, and decomposers.